(untitled) (Global Journal of Management and Business Research, 2019)
CSR and Ethics in business and government today are very important subjects. There are various reasons for businesses to operate in an ethical and socially responsible manner. There are government regulations, corporate belief systems, and basic common sense. There needs to be an overall intent to be ethical and socially responsible in today#x2019;s business environment in order to stay successful. In India keeping this in view many big corporate houses like TATA, Mahindra